دور صناديق الثروة السيادية في تعزيز التنمية الاقتصادية وتنويع مصادر الدخل دراسة تجربة إمارة دبي "مؤسسة دبي للاستثمارات الحكومية " - شبوطي, حكيم; محي الدين, سمير (جامعة الوادي - University of Eloued, 2017)
السيادية أداة من الأدوات المالية التي تملكها الحكومات، وتم إنشائها تحسبا لنضوب الموارد الطبيعية ولزيادة الطاقة الإستعابية وتنويع الاقتصاد ومواجهة تقلبات أسعار البترول، ودولة الإمارات العربية المتحدة أحد أهم الدول في العالم التي أنشأت صناديق للثروة السيادية، حيث تملك سبع صناديق بحجم أصول تقدر بـــــ1265.8 مليار دولار أمريكي ونسبة 17.19% من إجمالي أصول صناديق الثروة السيادية في العالم، وبنسبة 43.31% من إجمالي أصول الصناديق السيادية في دول مجلس التعاون الخليجي. يعد صندوق مؤسسة دبي للاستثمار المملوكة من حكومة دبي، حيث يملك الصندوق 33 شركة موزعة على عدة مجالات منها النقل، التمويل والاستثمار، الطاقة والصناعة، العقارات والإنشاءات..، وكان قطاع النفط والغاز في إمارة دبي يمثل نحو 55% من الناتج المحلي الإجمالي في عام 1981، لتصل إلى أقل من 2% في عام 2014، وكانت لهما دور بارز في إستراتيجية دولة الإمارات لتنويع الاقتصاد وتقليل من الاعتماد على البترول، وتعزيز التنوع القطاعي والتنمية. Sovereign wealth funds are a tool of financial instruments owned by Governments, have been established in anticipation of the depletion of natural resources and to increase the absorptive capacity and diversify the economy and cope with the vagaries of oil prices, the United Arab Emirates one of the most important countries in the world which have established sovereign wealth funds, which owns seven boxes estimated the size of total assets 1265.8 billion US dollars, and the proportion of 17.19% of the total assets of sovereign wealth funds in the world, and by 43.31% of the total assets of sovereign wealth funds in the Gulf cooperation Council (GCC). The Dubai Investment Corporation Fund is owned by the Government of Dubai. The Fund has 33 companies in various fields, including transport, finance and investment, energy, industry, real estate and construction .., he was representing the oil and gas sector in the Emirate of Dubai about 55% of GDP in 1981, to reach less than 2% in 2014, and has been for them a prominent role in the UAE's strategy to diversify the economy and reduce dependence on oil, And promoting sectoral diversification and development.
مقال
Keywords: صناديق الثروة السيادية، مؤسسة دبي للاستثمار الحكومي، تنويع الاقتصاد; Sovereign wealth funds, Dubai Government Investment Corporation , Diversification of the economy.